2018
DOI: 10.18502/jnfs.v3i4.166
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Spirulina Platensis Microalgae on Textural and Sensory Properties of Baguette Bread

Abstract: Background: Spirulina platensis is a photosynthetic microalgae with fibrous filamentous that belongs to the cyanobacteria family. In this study, we investigated the effects of ethanol and methanol extracts as well as the powder of spirulina platensis microelements on the sensory and texture properties of the bread. Methods: In order to determine the texture characteristics, we applied a texture analyser and conducted the Texture Profile Analysis test (Double-Density Compression). Sensory evaluation (hedonic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Current commercial food applications of T. chuii in the EU through novel food approval have been limited to sauces, condiments and salts albeit at a very limited maximum permissible addition level of 250 mg/serving/d (AECOSAN, 2017). Several other genera of dried green and blue-green (cyanobacteria) microalgae, and even an unidentified species of Tetraselmis (Lafarga, 2019), have been evaluated as experimental ingredients in wheat bread making with a proliferation of interest in the last five years (Ak et al, 2016;Finney, Pomeranz, & Bruinsma, 1984;García-Segovia, Pagán-Moreno, Lara, & Martínez-Monzó, 2017;Graça, Fradinho, Sousa, & Raymundo, 2018;Lafarga, 2019;Sanjari, Sarhadi, & Shahdadi, 2018;Tertychnaya, Manzhesov, Andrianov, & Yakovleva, 2019). Wheat flour replacement with microalgae up to 10% w/w have been investigated (Ak et al, 2016;Finney et al, 1984) although most studies tended to add less (1-5%) and often as a direct addition rather than a substitution of wheat flour.…”
Section: Introductionmentioning
confidence: 99%
“…Current commercial food applications of T. chuii in the EU through novel food approval have been limited to sauces, condiments and salts albeit at a very limited maximum permissible addition level of 250 mg/serving/d (AECOSAN, 2017). Several other genera of dried green and blue-green (cyanobacteria) microalgae, and even an unidentified species of Tetraselmis (Lafarga, 2019), have been evaluated as experimental ingredients in wheat bread making with a proliferation of interest in the last five years (Ak et al, 2016;Finney, Pomeranz, & Bruinsma, 1984;García-Segovia, Pagán-Moreno, Lara, & Martínez-Monzó, 2017;Graça, Fradinho, Sousa, & Raymundo, 2018;Lafarga, 2019;Sanjari, Sarhadi, & Shahdadi, 2018;Tertychnaya, Manzhesov, Andrianov, & Yakovleva, 2019). Wheat flour replacement with microalgae up to 10% w/w have been investigated (Ak et al, 2016;Finney et al, 1984) although most studies tended to add less (1-5%) and often as a direct addition rather than a substitution of wheat flour.…”
Section: Introductionmentioning
confidence: 99%
“…The bread sample with SPE-0.50 had higher scores in terms of crust color (3.9±0.1), crumb color (3.4±0.1), crumb pore size (3.8±0.2), crumb pore homogenity (3.6±0.0), bread shape (4.2±0.2), bread volume (4.4±0.0), acceptibility (3.6±0.1) and preferability (3.9±0.1) (p≤0.05, Table 5). In our study, Spirulina platensis and protein extracts from Spirulina platensis did not cause any negative effect on sensory properties of the breads since SP and SPE were used at low concentration compared to the literature (De Marco et al, 2014;Saharan and Jood, 2017;Sanjari et al, 2018). On the other hand, Sanjari et al (2018) reported that samples with Spirulina powder received the lowest sensory properties.…”
Section: Sensory Analysismentioning
confidence: 41%
“…The use of microalgae and cyanobacteria to improve the nutritional status of bread has been explored in different studies; with Spirulina platensis [ 2 , 3 , 7 ], Chlorella vulgaris [ 8 ], Tetraselmis chui [ 9 , 10 ] and Nannochloropsis gaditana [ 11 , 12 ]. Common for most studies, on the enrichment of bread with microalgae or cyanobacteria, is the small addition or wheat flour replacement level (1–5%), which are not sufficient for a big improvement in protein content or quality.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae acquire their dark green colour from pigments (chlorophyll). Some studies [ 7 , 13 , 18 ] have eliminated these pigments by extraction with ethanol. In a baguette, prepared with 1% ethanol-treated Spirulina platensis , sensory properties (colour, taste, and smell) were improved compared to the baguette with untreated algae [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation